CHARACTERISTIC OF PARAMETERS OF HEART RATE VARIABILITY IN PATIENTS WITH DIFFICULT-TO-CONTROL AND CONTROLLED ARTERIAL HYPERTENSION - Tymoshenko, O. S.; Yabluchansky, M. I.; Martynenko, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
Parameters of heart rate variability (HRV) were studied in 112 patients with arterial hypertension (AH) aged 58.5 ± 9 years (60 patients with difficult-to-control arterial hypertension (DTCAH) and 52 patients with controlled arterial hypertension (CAH)). The control group was consisted of 20 conditionally healthy persons of the same sex and age. It has been established that patients with AH were characterized by decrease in the level of total power of the HRV spectrum, the power of the high-frequency (HF) and low-frequency (LF) domains of the spectrum, and increase in the level of the very low-frequency spectrum (VLF) and value LF/HF that reflect sympathovagal balance. It has been established that there were more significant disorders in neurohumoral regulation in patients with DTCAH in comparison with patients with CAH, which consist of the predominant adrenergic activation, primarily due to the sympathetic link of the autonomic nervous system. HRV can be used as an effective non-invasive method for the diagnosis and control of DTCAH.